Mathematics Learning of High School Students and the Determinants of their Performance in the Midst of Pandemic - Andie Tangonan Capinding (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study focused on the determinants of Mathematics performance of high school students amidst pandemic. This was conducted at NEUST-Gabaldon Campus during the School Year 2020-2021. A descriptive-correlational design was used to explore the relationship of the students’ Mathematics performance with the factors that might affect the latter such as student’s factor, teachers’ factor, and parents/guardians’ factor. The 211 junior and senior high school students, four mathematics teacher, and 211 parents/guardians were used as respondents of the study. The student-respondents as well as the parent-respondents were selected using stratified sampling while the teacher-respondents were selected purposively. Findings revealed that most of the student-respondents are females and most of them are fifteen years old. Most of the students earned satisfactory to very satisfactory grades, demonstrated a variety of learning styles, and were inspired and enthusiastic about learning Mathematics. Teachers are also highly capable of delivering a lesson, as shown by their professional qualifications, number of trainings/seminars attended, number of years of experience, and use of variety of teaching strategies. Parents are also capable of educating their children but majority of them lack financial resources which limits their ability to improve their children's learning opportunities. The student's attitude, motivation, visual and auditory learning, the teacher's educational qualification and teaching style, and the parent's educational attainment and economic status were all observed as determinants of Mathematics success. Its theoretical and practical consequences were also discussed in the study.